Harmonizing digital innovations with Western opera: A literature review of audience development strategies - Michelangelo Galeati (IUL Research)
The convergence of technology and performing arts, particularly Western opera, has revolutionized audience engagement and development strategies. This literature review explores integrating digital innovations with traditional opera, aiming to enhance accessibility, interaction, and audience participation. Key areas examined include the shift from passive to interactive audience roles, the use of digital media to break down barriers and foster engagement, and case studies of Italian creative industries implementing these strategies. The study highlights the importance of understanding audience motivations, abilities, and opportunities to engage new and existing audiences effectively. It also underscores the role of digital tools in revitalizing public engagement and fostering community in the performing arts.